Comprehensive prognostic gene identification and functional characterization of GRAMD1A in Wilms tumor: development of risk prediction models and therapeutic implications - Zeng, Qiang; Tao, Junfeng; Qin, Lilu; Zeng, Yong; Liu, Zhong; Xu, Mingxian; Zeng, Linshan (Frontiers in Oncology, 2024)
BackgroundWilms tumor (WT) is the most common pediatric kidney cancer, with survival rates exceeding 90% in localized cases. However, advanced or recurrent WT remains difficult to treat due to poor prognosis and limited knowledge of its molecular mechanisms. Gene expression profiling has shown promise in identifying prognostic markers and therapeutic targets. This study aimed to identify key prognostic genes and pathways in WT, construct risk prediction models, and validate their role in tumor progression.MethodsRNA sequencing and clinical data from 136 WT patients were obtained from the TARGET database. Differential gene expression analysis was conducted using GEO datasets GSE11024 and GSE66405 to compare WT and normal kidney tissues. Identified differentially expressed genes (DEGs) underwent Gene Ontology (GO) and KEGG pathway enrichment analysis to explore biological functions and pathways associated with WT progression. Univariate Cox regression was used to assess the association between DEGs and overall survival (OS) and progression-free survival (PFS). LASSO regression models were developed for risk stratification, and model accuracy was evaluated using time-dependent ROC curves. External validation confirmed key hub genes, while functional assays in WT cell lines (WiT-49) assessed the role of GRAMD1A in tumor behavior.ResultsA total of 3,395 DEGs were identified, with 1,564 upregulated and 1,831 downregulated genes. Enrichment analyses revealed significant pathways involved in cell cycle regulation and metabolic reprogramming. Six key genes (GRAMD1A, PLXNA3, SPR, EBAG9, RBM47, and RIDA) were associated with both OS and PFS. LASSO models demonstrated strong predictive performance, with GRAMD1A identified as a major risk factor. External validation confirmed differential expression, and functional assays showed that GRAMD1A silencing significantly inhibited WT cell viability, proliferation, migration, and invasion.ConclusionsThis study identifies novel prognostic genes and potential therapeutic targets in WT. GRAMD1A, SPR, EBAG9, RBM47, and RIDA play critical roles in WT progression, with GRAMD1A as a key oncogenic factor, offering potential for risk stratification and future therapeutic intervention.